Government Information Systems in the Digitalization Era 4.0 in Increasing the Value of Human Resources. - Andika Prasetya Nugraha; Hutri Agus Romi; Mefri Yudi Wisra; Suci Suriani (Dinasti Publisher, 2024)
This study examines the role of Government Information Systems (SIP) in the era of digitalization 4.0 in increasing the value of Human Resources (HR). The research object focuses on the implementation of SIP in government organizations and its impact on productivity and human resource value. The main objective of this study is to analyze the influence of SIP on improving work efficiency and human resource value in the context of government in the digital era. The research method uses a quantitative approach with path analysis, examining the relationship between SIP, Digital Era 4.0, HR Productivity, and HR Value. Data was collected through surveys and analyzed using inferential statistical techniques. The results of the study show that SIP has a positive influence on HR Value, with HR Productivity acting as a mediating variable. However, the effect of this mediation is not statistically significant. SIP quality and integration were found to be key factors that affect system effectiveness in increasing productivity and HR value. This research highlights the importance of optimal SIP implementation and the need for an adaptive organizational culture to maximize the benefits of technology in improving HR performance in the government sector.